Hubungan asupan diet dengan penanda inflamasi pada penyandang obesitas - Martineta, Meriza; Sari, Dina Keumala; Tala, Zaimah Z; Lubis, Nenni Dwi Aprianti (Universitas Muhammadiyah Sumatera Utara, 2021)
Obesity is a body condition caused by an energy imbalance that is closely relatedto diet. Obese people experience chronic low-grade inflammation in the body that can lead tochronic disease due to the production of inflammatory markers from adipose tissue, one ofwhich is the acute phase protein C-reactive protein (CRP), which is closely related to diet.The purpose of this study was to determine the relationship between dietary intake andinflammatory markers (high sensitivity C-reactive protein, hs-CRP) in obese people. Therewere 34 men and women aged 19-59 years with BMI 25.0 kg/m2 tested for hsCRP blood andassessed dietary intake using the food frequency questionnaires (FFQ) method. Therelationship between dietary intake and hsCRP was assessed using the Spearman correlation.Intake of calories, protein, fat, carbohydrates, fiber, PUFA, and cholesterol did not have asignificant relationship with hsCRP (p 0.05). Dietary intake is not associated with hsCRP.